2012
DOI: 10.1590/s0100-879x2012007500159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hepatocyte growth factor and angiotensin II on rat cardiomyocyte hypertrophy

Abstract: Angiotensin II (Ang II) plays an important role in cardiomyocyte hypertrophy. The combined effect of hepatocyte growth factor (HGF) and Ang II on cardiomyocytes is unknown. The present study was designed to determine the effect of HGF on cardiomyocyte hypertrophy and to explore the combined effect of HGF and Ang II on cardiomyocyte hypertrophy. Primary cardiomyocytes were isolated from neonatal rat hearts and cultured in vitro. Cells were treated with Ang II (1 µM) alone, HGF (10 ng/mL) alone, and Ang II (1 µM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…The TGF-β type I receptor knockout induced an increase in Akt signalling and reduction in E3 ligase expression are likely mediated at least in part via elevated Hgf expression levels in myofibres. In both myoblasts and myotubes, HGF stimulates the Akt/mTOR pathway ( Chen et al, 2012 ; Perdomo et al, 2008 ). In addition, reduced Smad2/3 phosphorylation within myofibres likely contributes to the increase in Akt signalling and reduction in E3 ligase expression ( Goodman et al, 2013 ; Sartori et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β type I receptor knockout induced an increase in Akt signalling and reduction in E3 ligase expression are likely mediated at least in part via elevated Hgf expression levels in myofibres. In both myoblasts and myotubes, HGF stimulates the Akt/mTOR pathway ( Chen et al, 2012 ; Perdomo et al, 2008 ). In addition, reduced Smad2/3 phosphorylation within myofibres likely contributes to the increase in Akt signalling and reduction in E3 ligase expression ( Goodman et al, 2013 ; Sartori et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β type I receptor knockout induced an increase in Akt signalling and reduction in E3 ligase expression are likely mediated at least in part via elevated Hgf expression levels in myofibres. In both myoblasts and myotubes, HGF stimulates the Akt/mTOR pathway (A. L. Chen et al, 2012; Perdomo et al, 2008). In addition, reduced Smad2/3 phosphorylation within myofibres likely contributes to the increase in Akt signalling and reduction in E3 ligase expression (Goodman, McNally, Hoffmann, & Hornberger, 2013; Sartori et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the p38-MAPK pathway involves an inhibitor known as SB203580, which has been shown to prevent HGF-induced reactions and which have been shown to suppress myogenic MSCs differentiation. It has been found that HGF therapy involving cardiomyocytes could be administered for cardiac repair, in addition, HGF is reported to play a key role in cardiomyocyte hypertrophy, moreover, Ang II is shown to increase the rate of cardiomyocytes hypertrophy ( Chen et al., 2012 ; Liao et al., 2012 ). A recent experiment conducted in a culture containing placenta-derived multipotent cells with laminin releases a significant amount of HGF secretion via Avb3/CD61 integrin, an integrin that is abundantly expressed in MSCs, reduces apoptosis and reactive oxygen species (ROS) generation in tumor necrosis factor-induced cardiomyocyte ( Moghadam et al., 2016 ).…”
Section: Mscs Differentiation Into Cardiomyocytesmentioning
confidence: 99%
“…In recent years, angiotensin AT 1 receptor through Ang II has been implicated in the development of stretch-induced heart hypertrophy in several investigations, additionally, ET-1 may play a role since ET-1 in rat heart is released when endothelial cells are stretched, and it has been demonstrated to rise in the pressure ( Chen et al., 2012 ). As a result, Ang II is released, which in turn releases ET-1.…”
Section: Cardiovascular Mechanotransductionmentioning
confidence: 99%